2017
DOI: 10.1002/dmrr.2902
|View full text |Cite
|
Sign up to set email alerts
|

Is there sufficient evidence for a causal association between antiretroviral therapy and diabetes in HIV‐infected patients? A meta‐analysis

Abstract: The association of antiretroviral therapy (ART) with diabetes is inconsistent and varies widely across primary epidemiological studies. A comprehensive and more precise estimate of this association is fundamental to establishing a plausible causal link between ART and diabetes. We identified epidemiological studies that compared mean fasting plasma glucose (FPG) concentrations and proportions of diabetes and metabolic syndrome between HIV-infected patients naïve and exposed to ART. Mean difference in FPG conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 60 publications
2
36
0
Order By: Relevance
“…Evidence shows that PLHIV receiving ART are at increased risk of diabetes. A meta‐analysis found that PLHIV on ART had almost 4‐fold increased odds of having diabetes and, moreover, those on ART for > 18 months had significantly higher fasting plasma glucose (FPG) . Some antiretroviral drugs in particular, specifically zidovudine (ZDV), stavudine (d4T), didanosine (ddI), indinavir (IDV) and lopinavir (LPV), are thought to contribute to increasing FPG levels .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that PLHIV receiving ART are at increased risk of diabetes. A meta‐analysis found that PLHIV on ART had almost 4‐fold increased odds of having diabetes and, moreover, those on ART for > 18 months had significantly higher fasting plasma glucose (FPG) . Some antiretroviral drugs in particular, specifically zidovudine (ZDV), stavudine (d4T), didanosine (ddI), indinavir (IDV) and lopinavir (LPV), are thought to contribute to increasing FPG levels .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Brown et al [ 2 ] observed that the prevalence of diabetes was up to four fold higher in HIV-infected men exposed to HAART compared to HIV-negative men. A recent meta-analysis confirms the strong association between the use of anti-retroviral therapy (ART) and increased risk for diabetes [ 3 ]. Furthermore, HIV-infected individuals have been found to have higher rates of metabolic syndrome, dyslipidaemia and lipodystrophy when compared to subjects without HIV infection [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the development of diabetes mellitus in people living with HIV has also been shown to be contributed by the use of certain specific medications that are component of combination HAART regimens [18]. A meta-analysis conducted including 41 studies revealed that the risk of diabetes mellitus in PLWHIV was about four times more as compared with treatmentnaïve individuals, and has concluded HAART to be the single most important predictor of diabetes mellitus in people living with HIV [19].…”
mentioning
confidence: 99%